The Level of Religion Radicalism Understanding Among University Students in Banyumas Region - Rindha Widyaningsih; Kuntarto Kuntarto; Muhamad Riza Chamadi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2021)
Students as the nation’s next-generation and the academic community should have a global understanding of religious radicalism danger. However, recently, many national mass media have reported about the radical ideological infiltration targeting university students. The understanding level of religious radicalism among university students can be a consideration in mapping the potential for the spread of radical ideology. However, there are indications that many students understand religious radicalism. This study aims to determine and analyse the level of understanding of re- religious radicalism among university students in the Banyumas region. Research respondents totalled 350 people from four universities in the Banyumas region. The data collection method was through a closed questionnaire. The basis of the composition of the questionnaire question items is Bloom’s Taxonomy levels C1 and C2. The correct answer point is four, and the wrong answer is 0. The researcher divided the respondents’ understanding level into three categories: high, medium, and low. The results showed that understanding religious radicalism in students studying exact sciences was 67.54%. The understanding stage of religious radicalism in students studying social science was in the range of 67.89%. University students in the Banyumas region have an average of 67.71% or are in the medium category with a low threshold score.